JNK‐dependent gene regulatory circuitry governs mesenchymal fate. (14th July 2015) - Sahu, Sanjeeb Kumar; Garding, Angela; Tiwari, Neha; Thakurela, Sudhir; Toedling, Joern; Gebhard, Susanne; Ortega, Felipe; Schmarowski, Nikolai; Berninger, Benedikt; Nitsch, Robert; Schmidt, Marcus; Tiwari, Vijay K
Synopsis <boxed-text content-type="graphic" id="embj201490693-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Combining transcriptome analysis and patient data, this study illustrates how JNK signaling drives EMT progression via a panel of specific transcription factors, several of which are linked to EMT for the first time. JNK signaling is essential for progression of epithelial to mesenchymal transition (EMT). EMT relies on JNK‐dependent transcriptional reprogramming of many crucial EMT genes. JNK‐induced novel transcription factors are critically required for acquisition and maintenance of the mesenchymal fate. These novel factors are highly expressed in invasive cancer cells where they function in gene regulation to maintain metastatic identity. These factors were also induced during neuronal development and function in neuronal migration in vivo.